Nyuwun Slamet; Local Wisdom of Javanese Rural People in Dealing with Covid-19 Pandemic through Request in Slametan Rite - Mukhlas Alkaf; Andrik Purwasito; I Nyoman Murtana; Wakit Abdullah (Javanologi: International Journal of Javanese Studies, 2023)
Covid-19 pandemic effect has resulted in restlessness within community. Some are restless because of decreased job and business opportunities, fear of being infected with disease, fear of losing the closed and beloved one, etc. This article tries to raise a Javanese community’s local wisdom, Slametan. Slametan is a form of local wisdom existing within Javanese people containing an action functioning to be a medium to request God to give safety. In principle, slametan rite is one of human actions to communicate with the Creator. Through the rite, human beings feel that what they ask will be granted. Human beings doing this are also sure and suggested that those having done the rite will get safety and protection effect. This belief will further create self confidence and the feeling of secure among them in working and continuing the life.